Deskripsi Morfologi Penyakit pada Batang Buah Naga (Hylocereus sp.) dan Pengendaliannya Menggunakan Pestisida Nabati dari Serai Wangi (Cymbopogon nardus) - Indah Oktaviani; Ayu Octavia Tanjung Putri; Mesita Dwi Pebina (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Dragon fruit (Hylocereus sp.) is a plant introduced from America and started to be cultivated in several areas in Indonesia. The high consumer demand is one reason to increase dragon fruit production. However, during the growth period, dragon fruit plant stems are at high risk for disease. This study aims to describe the stem morphology of dragon fruit plants that are attacked by disease and to determine the effect of vegetable pesticides from Lemongrass Wangi (Cymbopogon nardus) in the cultivation area of the Lampung Province Agricultural Training Center (BPP). The research was divided into two stages, namely field observations using survey methods, and testing the application of vegetable pesticides on diseased plants. Observations made in the first stage included: stem morphological symptoms, disease attack frequency (FS), and disease attack intensity (IS). Observations on stem morphology showed that there were eight types of disease with different symptoms and causes, with an attack frequency of up to 100%. The highest percentage of disease attack intensity was caused by anthracnose (56.7%), and the lowest was brown rot (13.4%). Disease control trials using botanical pesticides were carried out on three diseases that attack almost all individual dragon fruit plants, namely: anthracnose, mosaic, and stem rot. The results showed a decrease in attack intensity on stem rot, mosaic, and anthracnose after four weeks of pesticide spraying.